TOXIC DILATATION OF THE COLON IN CHAGAS-DISEASE - Kobayasi, S.; Mendes, E. F.; Rodrigues, MAM; Franco, M. F. (Blackwell Science, 1992)
Toxic megacolon occurs in colitis of differing aetiology. This report describes 15 patients with chagasic megacolon with this complication. The clinical signs and symptoms in all patients were pain and progressive abdominal distension accompanied by fever, severe toxaemia and shock. Seven patients developed this clinical pattern after manual removal of faeces. The remaining patients had pain and abdominal distension followed by signs of severe toxaemia when first examined. Nine patients underwent total colectomy with ileostomy (one death), four partial colectomy (all died) and two received medical treatment (both died). At autopsy, three of the four patients undergoing partial colectomy had residual colitis and enteritis. The surgical procedure of choice for this complication of chagasic megacolon is total colectomy.